Ethno Medico Botanical study of Bhairu Devrai (sacred grove) Pat, Mandangad (International Journal of Food and Nutritional Sciences, 2022)
Devrai or Sacred grove is ancient protected areas for the sake of conservation. These groves areassociated with many beliefs and disbeliefs which create either fear or devotional attitude in peopleresulting in conservation of plants within it. Bhairu Devrai is also an similar structure of conserved forestby local tribes. Situated in Konkan region it is rich in its biodiversity. This Devrai comprises many plantspecies which are more or less used as medicinal plants and have with fauna associated with these plants.Present research was focused on Ethno Medico Botanical study of plants known and unknown by tribes ofPat, Mandangad.